Factors Associated with Musculoskeletal Disorders Among Female Readymade Garment Workers in Bangladesh: A Comparative Study Between OSH Compliant and Non-Compliant Factories - Nabi MH; Kongtip P; Woskie S; Nankongnab N; Sujirarat D; Chantanakul S (Dove Medical Press, 2021)
Mohammad Hayatun Nabi,1,2 Pornpimol Kongtip,2,3 Susan Woskie,4 Noppanun Nankongnab,2,3 Dusit Sujirarat,5 Suttinun Chantanakul2 1Department of Public Health, School of Health and Life Sciences, North South University, Dhaka, Bangladesh; 2Department of Occupational Health and Safety, Faculty of Public Health, Mahidol University, Bangkok, Thailand; 3Center of Excellence on Environmental Health and Toxicology, Bangkok, Thailand; 4Department of Public Health, Zuckerberg College of Health Sciences, University of Massachusetts Lowell, Lowell, MA, USA; 5Department of Epidemiology, Faculty of Public Health, Mahidol University, Bangkok, ThailandCorrespondence: Pornpimol KongtipDepartment of Occupational Health and Safety, Faculty of Public Health, Mahidol University, 420/1 Ratchawithi Road, Ratchathewi District, Bangkok, 10400, ThailandTel +66 26444070Fax +66 23548561Email pornpimol.kon@mahidol.ac.thPurpose: Musculoskeletal Disorders (MSDs) are one of the most common occupational diseases responsible for work restriction and absenteeism. The purpose of the study was to compare the prevalence of MSDs between ready-made garment (RMG) factories that are compliant versus non-compliant with International Labor Organization (ILO) based Occupational Safety and Health (OSH) standards, and to identify other factors associated with a higher prevalence of MSDs.Methods: A multicenter cross-sectional study was conducted among 410 randomly selected female workers (age: > 18 years; ≥ 1 year of work experience) from 12 randomly selected RMG factories in the Dhaka district of Bangladesh from February to December 2019. Factories were stratified as OSH compliant or non-compliant. Data were collected using a structured questionnaire consist of socio-demographic, work-related factors, and Nordic Musculoskeletal Questionnaire (NMQ) for MSD assessment. Robust Poisson regression was used to investigate the association of MSDs with OSH compliance, socio-demographic and other work-related factors.Results: Respondents’ mean age was 26.9 ± 5.9 years. A total of 235 (57%) of the workers reported musculoskeletal pain in at least one body part during the last month. Among the nine reported MSDs, the prevalence of lower back pain was highest (41%) followed by pain in the knees (33%). Multivariable analysis showed lower prevalence of any MSD among workers in OSH compliant factories [aPR = 0.43, 95% CI: 0.31– 0.58], and workers with regular working hours (8 hrs/day) [aPR = 0.79, 95% CI: 0.62– 1.00]. The risk of developing any MSD was significantly higher for age group 25– 30 years [aPR = 1.16, 95% CI: 1.01– 1.33] and age group ≥ 31 years [aPR = 1.21, 95% CI: 1.04– 1.1.39].Conclusion: The study found a high burden of musculoskeletal disorders among female RMG workers, especially those in non-OSH compliant factories that work long hours. Enforcement of minimum ILO-based OSH standards and introduction of low-cost interventions to improve working conditions in non-compliant factories would help sustain the pace of development in this sector in Bangladesh, and ensure the health of the women who work there.Keywords: Nordic Musculoskeletal Questionnaire, back pain, neck pain, knee pain, occupational health, garment factory, work-related, aging, International Labor Organization